1995
DOI: 10.1074/jbc.270.10.5089
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Sulfated Carbohydrate Unit Implicated in the Carbohydrate-Carbohydrate-mediated Cell Aggregation of the Marine Sponge Microciona prolifera

Abstract: Species-specific cell reaggregation in the marine sponge Microciona prolifera is mediated by an adhesion proteoglycan. Two interactions are involved in the process: a Ca(2+)-dependent homophilic binding between proteoglycan molecules and a Ca(2+)-independent binding between the molecule and cells. Both interactions are mediated by the glycan moieties of the proteoglycan. The interaction of the proteoglycan with itself has been characterized as a carbohydrate-carbohydrate interaction of multiple low affinity si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
99
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 0 publications
4
99
0
Order By: Relevance
“…Subsequently, this attribution was confirmed by NMR experiments of glyconectin hydrolysis fragments from GN2 (see accompanying article (40)). This is in agreement with previous work that identified a Py(4,6)Gal-containing oligosaccharide obtained by hydrolysis of glyconectin from M. prolifera (28). The stability of the 4,6-O-(1-carboxyethylidene)-galactose pyranose ring to methanolysis (27) enabled us to estimate, among the other monosaccharides, the amount of this particular component in each sample (Table I).…”
Section: Purification and Physical Characterization Of Glyconectins Ofsupporting
confidence: 77%
See 2 more Smart Citations
“…Subsequently, this attribution was confirmed by NMR experiments of glyconectin hydrolysis fragments from GN2 (see accompanying article (40)). This is in agreement with previous work that identified a Py(4,6)Gal-containing oligosaccharide obtained by hydrolysis of glyconectin from M. prolifera (28). The stability of the 4,6-O-(1-carboxyethylidene)-galactose pyranose ring to methanolysis (27) enabled us to estimate, among the other monosaccharides, the amount of this particular component in each sample (Table I).…”
Section: Purification and Physical Characterization Of Glyconectins Ofsupporting
confidence: 77%
“…The distinct functional and physicochemical properties of this compound suggested that although it shares the general features of proteoglycans such as large size and long, sulfated, negatively charged glycans, it could define a new class of primordial cell recognition and adhesion proteoglycan-like glycoconjugates, named glyconectins. Recently reported partial sequence analysis of the carbohydrate moiety of the M. prolifera glyconectin 1 demonstrated new structural features distinct from glycosaminoglycans (17,24,28). The use of Block 1 and 2 monoclonal antibodies established the role of 1 sulfated and 1 pyruvated saccharide unit in the carbohydrate-carbohydrate self-interaction of GN1 (14, 15, 17, 28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These antibodies bind to highly repetitive epitopes (1,100 antigenic sites for Block 1 Fab [4], and 2,500 sites for Block 2 Fab [5]) located on the acidic g-200 glycan. Structural analysis of the isolated epitopes showed a pyruvated trisaccharide β-DGalp4,6(R)Pyr-(1→4)-β-D-GlcpNAc-(1→3)-L-Fucp 2 [6] (Block 1) and a sulfated disaccharide β-D-GlcpNAc3S-(1→3)-L-Fucp 1 [7] (Block 2) (Scheme 1). Additional studies on the biopolymer level revealed that the g-200 polysaccharide contains only α-L-Fucp units [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, their precise structure is still largely unknown. Only four short oligosaccharides, generated by mild hydrolysis of GN1, have been characterized as a new type of pyruvilated and sulfated oligosaccharide sequences, but their arrangement within the glycan moiety is unknown (11,12). These initial sequence analyses of GN1 glycans, represented mainly by two macromolecular species with molar masses of 200 and 6 kD (1, 2), revealed that they represent a novel class of acidic and fucose-containing polysaccharides different from those of classical glycosaminoglycans.…”
mentioning
confidence: 99%